Evolusi Peleburan Paraffin Sebagai Material Penyimpan Kalor (Studi Kasus Pada Model Tube-and-shell Versus Model Cone-and-shell) - Agus Dwi Korawan (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2019)
Paraffin as a heat storage material has many advantages, including good thermal properties, safe to use because it is not easy to react, and inexpensive. In this study, the paraffin was applied to the tube-and-shell and cone-and-shell type heat storage. The observed process is the paraffin melting process, which is done by taking pictures with digital cameras in both types during the melting process, taking pictures every 45 minutes from the beginning until the completion of the melting process. The results show that the paraffin melting in the tube-and-shell model occurs first, but the paraffin smelting is finished faster in the con-and-shell model.